2009
DOI: 10.1002/elps.200900087
|View full text |Cite
|
Sign up to set email alerts
|

Recursion approach for moving neutralization boundary formed on IPG strips Part I: With strong alkali rehydration buffer

Abstract: Moving neutralization boundary (MNB) is an important foundation to understand and improve IEF. However, there are obstacles in theoretical predictions of MNB on IPG strips due to the unknown local concentrations of carrier ampholytes on commercial IPG strips and the time-varying boundary velocities. We introduce a recursion approach to extend the current MNB theories into the space-time varying MNB system. The recursion approach emphasizes the localizability of physicochemical parameters in the discrete time i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 40 publications
0
18
0
2
Order By: Relevance
“…The reaction led to the formation of MNB. There was always a 1:1 equivalence-point chemical reaction between the H 1 and OH À in the EABT system whether the boundary moved toward the the anode or the cathode, or remained stationary [23,24]. Furthermore, such an equivalence-point reaction between the H 1 and OH À is present in the EABT system at any time.…”
Section: Experimental Model Of Eabtmentioning
confidence: 97%
See 4 more Smart Citations
“…The reaction led to the formation of MNB. There was always a 1:1 equivalence-point chemical reaction between the H 1 and OH À in the EABT system whether the boundary moved toward the the anode or the cathode, or remained stationary [23,24]. Furthermore, such an equivalence-point reaction between the H 1 and OH À is present in the EABT system at any time.…”
Section: Experimental Model Of Eabtmentioning
confidence: 97%
“…The concept of MRB is very useful in the field of electrophoresis. For example, the dynamic theory of isoelectric focusing (IEF) has been well developed from the concept of MNB [23,24,29]. It has been revealed that (i) IEF is based on the physical chemical model of MNB [23,24,29] and (ii) a series of historic issues (viz.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations